Pothea berengeri sp. nov. from Brazil, with taxonomic notes on Pothea furtadoi Gil-Santana & Costa and Pothea jaguaris (Carpintero) and reinstatement of Parapothea Carpintero as junior synonym of Pothea Amyot & Serville (Hemiptera: Heteroptera: Reduviidae: Ectrichodiinae) - Gil-Santana, Hélcio R. (Zootaxa, 2014)
Pothea berengeri sp. nov. from Brazil is described based on male and female specimens. Based on intraspecific variation of Parapothea jaguaris and morphological similarities with the species of Pothea studied, the monotypic genus Parapothea Carpintero is reinstated as a junior synonym of Pothea Amyot & Serville with the subsequent combination Pothea jaguaris (Carpintero). Intraspecific morphological and color variations of Pothea jaguaris (Carpintero) and Pothea furtadoi Gil-Santana & Costa are documented and discussed. Male genitalia of all three species are described and illustrated. Pothea jaguaris is recorded from French Guiana for the first time and comments on its sexual dimorphism are provided.